The Application of Digital Leadership of Subdistrict Head on Public Service Performance with the Delegation of Regent/Mayor Authorities as the Moderating Variable - Dwi Mardiana (Airlangga Development Journal, 2020)
The   low   Human   Development   Index   (HDI)   for   the   protected   areas   is   a  government-focused development  priority,  especially  in  the  health  sector.   Attempts  should  be  made  to  enhance  the  efficiency  of regional public services related to efforts to break the chain of Covid-19. Subdistrict heads have also contributed  greatly  to  the  optimization  of  task  assignments  to  the  apparatus.  An  appeal  to  implement  social  distancing becomes an obstacle for the subdistrict head for there is no face-to-face meeting with the assigned apparatus. The  subdistrict  heads  are  required  to  be  able  to  adapt  to  the  situation.  Thus,  the  subdistrict  heads  must  use digital  media  in  carrying  out  their  duties.  The  leadership  style  that  influences  service  performance  and  is appropriate to be implemented in this phenomenon is digital leadership. Meanwhile,  the  delegation  of authority   is  a  variable  that  might  strengthen  the  influence  of leadership on the performance of public services.  This study  aims  to  investigate  the  effect  of  the  subdistrict  head’s  digital  leadership  on  the  performance  of  public service employees in the subdistricts  of  Pendalungan  with  the  delegation  of  regent/mayor  authority  as  a moderating variable.